Reducing Carbon Emissions in The Indonesian Logistics Industry: A Delphi Study - Simarmata, Jeremy Ephraim; Simarmata, Jean Sebastian; Simarmata, Juliater; Octaviani, Reni Dian (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2025)
The logistics and transport industry significantly contributes to global carbon emissions, underscoring the urgent need for technological and regulatory interventions to mitigate its environmental impact, as outlined in the Paris Agreement. This study investigates strategies for reducing carbon emissions within Indonesia's logistics sector using the Delphi method. Key areas explored include vehicle age regulation, incentives for electric vehicle (EV) adoption, and the enhancement of biofuel usage. By gathering expert insights from industry leaders, regulators, and academics, the research addresses crucial issues and identifies effective solutions. The findings reveal a consensus on the pivotal role of EVs in mitigating carbon emissions and emphasize the necessity of supportive policies and infrastructure to enable this transition. The study also evaluates the effectiveness of low emission zones and the potential of biofuels as alternative energy sources. Results indicate that while the adoption of EVs and biofuels offers significant benefits, challenges such as high costs and insufficient infrastructure remain substantial barriers. Furthermore, the research highlights the need for robust regulatory frameworks and financial incentives to foster the adoption of cleaner technologies. This study enhances understanding of carbon reduction strategies in the logistics industry and offers actionable recommendations for policymakers and business leaders to expedite the transition to a more sustainable and low-carbon logistics sector in Indonesia.